I have painted about how the beings can transform themselves (2014)
The paintings of Enrique Casanto, ashaninka from the Orchid clan, make you see double because they show that everything that exists has its double. Everything is at the same time human and not-human, including himself and all those of the Casanto clan, descending from the great Orchid warrior of the past who used the strategies of a flower quietly resting on a branch to defeat his enemies. Being so much like an orchid, he ended up transforming in to such a plant. His art shows the passage from one shape to the other as it takes place in cosmology and shamanism.